Improvement of digital lensless holographic microscopy for the visualization of biosamples (2023)
Digital Lensless Holographic Microscopy (DLHM) is an imaging technique that has been used to visualize micrometer-sized samples. The simplicity of the required hardware, the adaptability of digital processing, and its label-free attribute have positioned it as an attractive, portable, and cost-effective alternative for observing microscopic biological samples. Despite the simplicity of its implementation, the hardware used to record the digital holograms has limitations that directly affect the visualization of biological samples. In this master’s thesis in Engineering Physics, the identified limitations of the DLHM hardware and their impact on the visualization of micrometer-sized objects are studied. An improvement of those limitations is proposed by implementing opto-numerical methods, which are tested by visualizing biosamples. Given the importance of the Numerical Aperture (NA) for the performance of DLHM, a method for characterizing and validating the NA of propagating beam illuminations is developed. A method for expanding the field of view of the visualized samples is presented. Finally, a multiview method for correcting DLHM in-line holograms is proposed to eliminate illumination artifacts inherited from the illumination source, and also to recover the information of occluded structured samples visualized in DLHM. The results were reported on two manuscripts already published in indexed journals of international circulations and five proceedings or submitted abstracts of presentations at international conferences.